The Nexus of Carcerality and Access and Success in Postsecondary Education. (September 2022) - Huerta, Adrian H.; Britton, Tolani
This special issue of American Behavioral Scientist focuses on college preparation, access, and success for individuals impacted by carceral systems and practices in K-12 and higher education. Carcerality is (in)formal rules that center discipline, punishment, and control of individuals. Most recently, the embodiment of carceral practices has become more visible throughout the educational system, particularly for students of color. Attitudes, practices, and policies shape how K-12 and higher education students are perceived and treated as risks. In turn, these attitudes and policies lead to decisions about whether students merit investments that increase the likelihood of success in the education system. In the face of these structural barriers, students resist and overcome these policies and the systemic underinvestment in their education. This volume of articles centers the interconnection between education and criminal (in)justice to understand how both fields interact and position minoritized students in the social, academic, and behavioral margins. Articles explore the experiences of system-impacted students in K-12, higher education, theoretical application of risk, the impact of carceral laws and policies on educational access, and response to practices and policies that can counter carceral efforts in education systems.